2015
DOI: 10.4103/0366-6999.159345
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of High Fibrinogen and Low High-density Lipoprotein Cholesterol Levels Predicts Recurrent Cerebral Venous Thrombosis

Abstract: Background:Cerebral venous thrombosis (CVT) may lead to serious neurological disorders; however, little is known about the risk factors for recurrent CVT. Our aim was to determine the association between elevated fibrinogen and decreased high-density lipoprotein cholesterol (HDL-C) levels with recurrent CVT.Methods:This retrospective cohort study included participants if they had a first episode of objectively defined CVT and were admitted to Xuan Wu Hospital, Capital Medical University from August 2005 to Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Thrombosis, and therefore hypercoagulation, is typically associated with increased levels of fibrin(ogen) [ 58 , 70 , 71 ]. A changed iron profile (e.g.…”
Section: Oxidative Damage Iron Inflammation and Hypercoagulabilitymentioning
confidence: 99%
“…Thrombosis, and therefore hypercoagulation, is typically associated with increased levels of fibrin(ogen) [ 58 , 70 , 71 ]. A changed iron profile (e.g.…”
Section: Oxidative Damage Iron Inflammation and Hypercoagulabilitymentioning
confidence: 99%
“…A prior study by Ma et al [ 19 ] demonstrated a correlation between concurrent increases in FIB and declines in HDL levels and an increased risk of recurrent cerebral thrombosis, whereas the separate evaluation of FIB and HDL levels did not yield significant results. According to a study by Kowalski et al [ 30 ], the co-occurrence of elevated D-dimer, a breakdown product of FIB, and lower HDL levels appeared to contribute to the progression of acute pulmonary emboli.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, despite the contrasting significance of FIB and HDL in relation to coagulation and inflammatory alterations, their combined role in mortality prediction among patients with AMI remains largely unexplored. To date, limited studies have explored the coexistence of elevated FIB values and decreased HDL that were associated with recurrent cerebral venous thrombosis (CVT) among those previously diagnosed with CVT [ 19 ]. Additionally, this combination was closely correlated with the onset of CVD among diabetes patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, blueberry improves lipid profiles and can inhibit CVT development. Low level of HDL-C has been found to be associated with recurrence of CVT (Ma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%